Legal Mechanisms for Counteracting Tax Evasion at The International Level - Nataliia Strutovska (Emerging Frontiers Library for The American Journal of Political Science Law and Criminology, 2025)
The article presents a broad-based analysis of legal mechanisms for counteracting tax evasion at the international level. The study is based on an interdisciplinary approach that incorporates elements of international tax law, public law, economics, and institutional theory. It examines legal mechanisms for resolving tax disputes, ranging from arbitration under bilateral agreements and OECD multilateral instruments to the procedures of the World Trade Organization, highlighting their advantages and limitations. A separate section is devoted to the challenges of the digital economy: the limitation of tax sovereignty in developing countries due to trade agreements, the conflict between the EU and the US regarding data taxation, and the concept of digital constitutionalism as a prospective normative framework. Particular attention is paid to the role of micro-actors—tax consultants and professional intermediaries—who shape the functioning of transnational schemes and require inclusion in the system of international regulation. The dual effect of reforms is emphasized: on the one hand, strengthening institutional mechanisms to combat tax evasion, and on the other, generating new market risks and institutional collisions. The article substantiates the need to shift toward an actor-centered approach, in which the regulation of intermediaries and the development of normative principles for the digital era become prerequisites for the sustainability of the global tax regime. The material will be of interest to researchers in international law, economics, and finance, as well as to specialists engaged in the development and implementation of global tax regulation mechanisms.